Mendeteksi Earnings Management Perusahaan Melalui Aktivitas Riil - Viriany; Liana Susanto; Henny Wirianata; Yanti (Jurnal Ekonomi, 2020)
This research was to obtained empirical evidence about the influence of leverage, profitability, institutional ownership, independent commissioner, audit committee to the Real Earnings Management of the manufacturing companies listed at the Indonesian Stock Exchange from 2015-2017.This research uses 64 companies that were selected using purposive sampling method. In this study, the hypotheses tested using the multiple regression model.The results showed that only profitability has significant influence.